Farmers’ Participatory Plant Selection of Lablab (Lablab purpureus (L.) Sweet) in Tanzania - Letting, Fanuel K.; Venkataramana, Pavithravani B.; Ndakidemi, Patrick A. (Frontiers in Plant Science, 2022)
Farmer-participatory breeding approach is an important component in the crop improvement of lablab (Lablab purpureus). The study was carried out to obtain the knowledge, practices and preferences of lablab through 31 lablab growing farmers from Arusha, Kondoa, Karatu, Same and Babati districts of Tanzania towards initiating a lablab breeding program. Semi-structured questionnaires were administered and focused group discussions were held to collect data on the socio-demographic factors, production practices, constraints and farmer's preferred traits of lablab. Selection of preferred traits and accessions was also done by the farmers in the field. Results showed that the chief constraints of lablab production are pests and diseases, poor marketability, low seed quality, inadequate rainfall, expensive agrochemicals, low yield and poor storage facilities. The major pests are pod borer (field) and bruchids (storage). Preferred traits for lablab improvement include the development of insect pests and disease-resistant varieties, early maturing, high yield, black coloured seed for market, short cooking time, and dense foliage. Genotypes EK2, D360, HA4 and D96 with preferred traits were identified by farmers, which forms critical decisions in crop improvement. This study describes the current view of lablab production and generates the understanding of farmers’ perceptions and preferences vital for breeding priorities and programs to increase its production, utilization and consumption.